Beyond purified dietary fibre supplements: Compositional variation between cell wall fibre from different plants influences human faecal microbiota activity and growth in vitro - Michael Solvang; Freda M. Farquharson; Dayan Sanhueza; Graham Horgan; Wendy R. Russell; Petra Louis (Environmental Microbiology, 2023)
Dietary fibre is a major energy source for the human gut microbiota, but it is unclear to what extent the fibre source and complexity affect microbial growth and metabolite production. Cell wall material and pectin were extracted from five different dicotyledon plant sources, apples, beet leaves, beetroots, carrots and kale, and compositional analysis revealed differences in the monosaccharide composition. Human faecal batch incubations were conducted with 14 different substrates, including the plant extracts, wheat bran and commercially available carbohydrates. Microbial activity was determined for up to 72 h by measuring gas and fermentation acid production, total bacteria (by qPCR) and microbial community composition by 16S rRNA amplicon sequencing. The more complex substrates gave rise to more microbiota variation compared with the pectins. The comparison of different plant organs showed that the leaves (beet leaf and kale) and roots (carrot and beetroot) did not give rise to similar bacterial communities. Rather, the compositional features of the plants, such as high arabinan levels in beet and high galactan levels in carrot, appear to be major predictors of bacterial enrichment on the substrates. Thus, in‐depth knowledge on dietary fibre composition should aid the design of diets focused on optimizing the microbiota.